Young Men's Health Matters: Implementing a Community-Academic Partnership in an Urban Federally Qualified Health Center - Jade Burns PhD, RN, CPNP-PC; Jaquetta Reeves PhD, MS, BSN, RN, NP-C; Mackenzie Adams MPH; Gabrielle Darville-Sanders PhD, MPH; Keith A. Johnstone BBA; Rico Ozuna-Harrison BA; Kedar Johnson BSN; Derek Ware BA; George H. Shade MD, FACOG, FACPE; Wayne W. Bradley BA (SAGE Publishing, 2022)
Community-based participatory research (CBPR) approaches are being leveraged more and more in efforts to improve health equity. Informing the building of community-academic partnerships, CBPR draws on the community's expressed needs and engages stakeholders in future intervention development. To date, however, little has been published on such efforts targeting the health of young Black men (ages 18-24), despite this population's disproportionate need. In this paper, we describe the formation of a community-academic partnership in a federally qualified health center, with the goal of improving the health of young Black men in Detroit, Michigan. After conducting a needs assessment, we built upon existing networks to form a Community Advisory Board (CAB). We held three community forums during which CAB members highlighted key health issues in their community and described how they could be addressed. We developed a plan for future research and community engagement based on community input. Finally, we provide insights on community engagement strategies, forum structure, setting boundaries, trust-building, and valuable information in addressing the inequities in health that affect young Black men.